The Popular Culture of Upin & Ipin and Adit & Sopo Jarwo Animated Series - Adjikusuma, Evelyna Nissi; Dukut, Ekawati Marhaenny (Celt: A Journal of Culture, English Language Teaching & Literature, 2022)
Popular culture refers to a culture enjoyed by the mass because it is closely related to people’s lives. One such pop culture product is film. In this paper, the the main data for discussion is a Malaysian animated series, Upin Ipin and the Indonesian animated series, Adit Sopo Jarwo The first episode of Upin Ipin and the two episodes of Adit Sopo Jarwo are used to see how the series used popular culture strategies to maintain their popularity, and how through analyzing the plot, similar moral values are found. The method used to analyze is s Roland Barthes’ semiotics. The result of the research showed  that both animated series were the products of pop culture because the series fulfilled the characteristics of satisfying viewers, easy  to obtain, showed an eagerness to please viewers, and  reflected the culture of the Malaysian and Indonesian society. Two similar moral values which were obedience and gratefulness were found in those animated series. The obedience was shown through young characters who were not scared to confront  older people, but also show how to respect  elders . Gratefulness in the series in the animated series were found through seeing the characters see the positive sides of life